2018
DOI: 10.3390/ijms19092692
|View full text |Cite
|
Sign up to set email alerts
|

Comparative In Vitro and In Silico Analysis of the Selectivity of Indirubin as a Human Ah Receptor Agonist

Abstract: The aryl hydrocarbon receptor (AhR) is a ligand-dependent transcription factor that modulates gene expression following its binding and activation by structurally diverse chemicals. Species differences in AhR functionality have been observed, with the mouse AhR (mAhR) and human AhR (hAhR) exhibiting significant differences in ligand binding, coactivator recruitment, gene expression and response. While the AhR agonist indirubin (IR) is a more potent activator of hAhR-dependent gene expression than the prototypi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 55 publications
0
35
0
Order By: Relevance
“…According to this hypothesis, the synthesis of 6'-bromoindirubin (2h) and 3-bromotryptanthrin (3h) seems to be favored compared to Studies from several laboratories have demonstrated that indirubin is a highly potent and efficacious human-selective AhR agonist that induces AhR-dependent gene expression in human cells with an EC50 that is ~10-fold greater than that of TCDD. 3,34,35,76 In contrast, in mice or mouse cells, indirubin is ~100-less less potent than TCDD, but still highly efficacious. 34,35,76 Site-directed mutagenesis and functional analysis studies have identified specific amino acid residues within the mouse and human AhR ligand binding pockets that contributes to this differential specificity and responsiveness.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…According to this hypothesis, the synthesis of 6'-bromoindirubin (2h) and 3-bromotryptanthrin (3h) seems to be favored compared to Studies from several laboratories have demonstrated that indirubin is a highly potent and efficacious human-selective AhR agonist that induces AhR-dependent gene expression in human cells with an EC50 that is ~10-fold greater than that of TCDD. 3,34,35,76 In contrast, in mice or mouse cells, indirubin is ~100-less less potent than TCDD, but still highly efficacious. 34,35,76 Site-directed mutagenesis and functional analysis studies have identified specific amino acid residues within the mouse and human AhR ligand binding pockets that contributes to this differential specificity and responsiveness.…”
Section: Discussionmentioning
confidence: 99%
“…3,34,35,76 In contrast, in mice or mouse cells, indirubin is ~100-less less potent than TCDD, but still highly efficacious. 34,35,76 Site-directed mutagenesis and functional analysis studies have identified specific amino acid residues within the mouse and human AhR ligand binding pockets that contributes to this differential specificity and responsiveness. 35 The similarities in structual aspects of indirubins and tryptanthrins suggest that similar species differences in tryptanthrin ligand specificity may also exist.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations